A review of state of health and remaining useful life estimation methods for lithium-ion battery in electric vehicles: Challenges and recommendations. (20th December 2018) - Lipu, M.S. Hossain; Hannan, M.A.; Hussain, Aini; Hoque, M.M.; Ker, Pin J.; Saad, M.H.M.; Ayob, Afida
Abstract: Electric vehicles (EVs) have become increasingly popular due to zero carbon emission, reduction of fossil fuel reserve, comfortable and light transport. However, EVs employing lithium-ion battery are facing difficulties in terms of predicting accurate health and remaining useful life states due to various internal and external factors. Currently, very few papers are addressed to summarize the state of health (SOH) and remaining useful life (RUL) estimation approaches. In this regard, the goal of this paper is to comprehensively review the different estimation models to predict SOH, and RUL in a comparative manner. The results identify the classifications, characteristics and evaluation processes with advantages and disadvantages for EV applications. The review also investigates the issues and challenges with possible solutions. Furthermore, the review provides some selective proposals for the further technological development of SOH, and RUL estimation for lithium-ion batteries. All the highlights insight this review will hopefully lead to the increasing efforts towards the development of the advanced SOH and RUL methods for future EV uses. Highlights: A comprehensive review of the methods to estimate SOH and RUL. A detailed investigation of the key issues and challenges of SOH and RUL. The highlight of effective solutions to address the challenges. Selective suggestions for the further development of SOH and RUL.